Prefoldin subunit 6 of Plasmodium falciparum binds merozoite surface protein‐1. Issue 5 (29th March 2022) - Kumar, Vikash; Shoaib, Rumaisha; Behl, Ankita; Munjal, Akshay; Abid, Mohammad; Singh, Shailja
Abstract : Malaria is a human disease caused by eukaryotic protozoan parasites of the Plasmodium genus. Plasmodium falciparum ( Pf ) causes the most lethal form of human malaria and is responsible for widespread mortality worldwide. Prefoldin is a heterohexameric molecular complex that binds and delivers unfolded proteins to chaperonin for correct folding. The prefoldin PFD6 is predicted to interact with merozoite surface protein‐1 (MSP‐1), a protein well known to play a pivotal role in erythrocyte binding and invasion by Plasmodium merozoites. We previously found that the P. falciparum ( Pf ) genome contains six prefoldin genes and a prefoldin‐like gene whose molecular functions are unidentified. Here, we analyzed the expression of Pf PFD‐6 during the asexual blood stages of the parasite and investigated its interacting partners. Pf PFD‐6 was found to be significantly expressed at the trophozoite and schizont stages. Pull‐down assays suggest Pf PFD‐6 interacts with MSP‐1. In silico analysis suggested critical residues involved in the Pf PFD‐6‐MSP‐1 interaction. Our data suggest Pf PFD‐6 may play a role in stabilizing or trafficking MSP‐1. Abstract : Prefoldin is a cochaperone that delivers unfolded proteins to chaperonin for proper folding. Here, we have characterized prefoldin‐6 subunit (PfPFD‐6) of Plasmodium falciparum . PfPFD‐6 is expressed during asexual blood stages and interacts with merozoite surface protein‐1 (MSP‐1), a key protein involved in erythrocyte invasion by the malaria parasite. Our study suggests that PfPFD‐6 may play a role in stabilizing or trafficking MSP‐1.